(untitled) - Graham Workman (Oxford, 1998)
The book introduces multi-word verbs and idioms in levely and memorable contexts. It provides work designed to encourage learners to explore collocation. The book contains twelve self-standing units, tapescripts, and an explanatory answer key
Keywords: english language - idioms,english language - spoken english - problems, exercises, etc,english language - textbooks for foreign speakers,english language - verb phrase,listening - problems, exercises, etc